Agricultural mechanization services, rice productivity, and farm/plot size: Insights from Myanmar - Myanmar Agriculture Policy Support Activity (MAPSA) (International Food Policy Research Institute, 2023)
The relationship between productivity and farm size has been at the center of considerable debate. Agricultural mechanization – that is rapidly taking off in a large number of low- and middle-income countries – has been identified as one of the emerging technologies in these settings with a critical, yet complex, influence on this productivity-size relation. However, knowledge gaps remain as how agricultural transformation due to the adoption of new technologies and the change in factor costs, such as mechanization fees, are associated with this productivity - size relation. In the case of Myanmar, where mechanization use has dramatically increased over the last decade, we find a significant inverse productivity - plot size relationship, with small rice plots having productivity levels approximately 30 percent higher than large plots. However, rising mechanization fees – more so in conflict-affected townships – attenuated this inverse relation between rice productivity (yield and profit per land) and plot size substantially. These results primarily hold on the largest rice plot cultivated by each farmer, but also generally hold when comparing total rice area and major non-rice area. Our results are likely explained by the fact that, in Myanmar, smallholders have become more dependent on mechanization services than larger farms (who can rely on their own machines) do, that alternatives to mechanization services have become scarce (as mechanization use changed little, despite these price increases), and that mechanization service costs account for a significant share of the total production costs among smallholders.